A Comparison of Traditional Book Reviews and Amazon.com Book Reviews of Fiction Using a Content Analysis Approach - Christy Sich (Evidence Based Library and Information Practice, 2017)
Objective - This study compared the quality and helpfulness of traditional book review sources with the online user rating system in Amazon.com in order to determine if one mode is superior to the other and should be used by library selectors to assist in making purchasing decisions.